Seven new records Arctiini (Lepidoptera: Erebidae: Arctiinae) to Peru - Grados, Juan (2013)
Seven new Arctiini (Erebidae: Lepidoptera) are reported for Peru. Some of the species are rare among collections. Each new report belongs to different genera and the species given for each genus are those occurring in Peru, according to collections and literature references from their original descriptions. A new synonym is also reported for Agyrtiola niepeltiGaede, 1926.